CORRELATION OF KNOWLEDGE AND ATTITUDES WITH FIRE EMERGENCY RESPONSE PREPAREDNESS IN THE COMMUNITY OF SEKARAN VILLAGE, LAMONGAN DISTRICT - Firnanda, Ega Delia Rizqah; Porusia, Mitoriana (HEARTY, 2024)
Sekaran Lamongan Village is a densely populated settlement where some of the residents work as smoked fish traders. During the fish smoking process, corncobs are used as fuel. This can increase the room temperature and potentially cause a fire. Fire emergency response preparedness in places that have a higher risk is needed for residents. Therefore, the knowledge and attitude towards fire management is very necessary to be owned by the community. This study aims to analyse the correlation between knowledge and attitude with fire emergency response preparedness in the community of Sekaran Village, Lamongan Regency. This research method uses analytical observations with a cross sectional approach. The independent variables in this study are knowledge and attitude, while the dependent variable is fire emergency response preparedness. The sample in this study was 322 residents of Sekaran Village with proportional random sampling technique for each neighbourhood. The research instrument used questionnaires for the independent and dependent variables. The results showed that there was a correlation between knowledge and fire emergency response preparedness (CI 95%: 0.077- 0.296). OR 0.151, and there is a correlation between attitude and fire emergency response preparedness (CI 95%: 0.312 - 0.761), OR 0.488. The better the knowledge and attitude, the better the emergency response preparedness.